Na poeira do nosso passado: perfil sociopolítico do Poder Legislativo do Estado da Paraíba (1990 a 2018) - Pompeu, José Mauro de Pontes (2021)
This dissertation aims to investigate the profile of those elected to the Legislative Assembly of Paraíba between 1990 and 2018, in order to grasp, on the one hand, common provisions among representatives and, on the other, to understand any sociopolitical changes in parliamentary recruitment . To identify, map and analyze the sociopolitical profile and trajectory of state deputies in Paraíba, a quantitative methodology was adopted, based on the analysis of descriptive statistics of the information obtained by the Election History System of TRE-PB and TSE, and prosopography as research and analysis technique. Although our conclusion confirms the overrepresentation of male individuals, with high levels of education and relative wealth, the proposition of our work is that the study of those elected to the Legislative can contribute to a better understanding of changes in the relationship between society -State.